The effect of Canva-assisted guided inquiry on students’ creativity and conceptual understanding in environmental change learning: A quasi-experimental - Amalia, Lida; Muthmainnah, Rifaatul; Soviawati, Siti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2026)
In the 21st century, science education must not only promote conceptual mastery but also cultivate creativity and higher-order thinking skills to address global challenges such as sustainability and environmental change. However, students often struggle to connect scientific knowledge with real-world contexts, leading to fragmented understanding and limited opportunities for creative expression. This study investigates the effectiveness of guided inquiry assisted by Canva, in enhancing both conceptual understanding and creativity in environmental change learning. The novelty of this research is the use of Canva-assisted guided inquiry as an integrated approach to develop both higher-order conceptual understanding and creativity aligned with 21st-century learning demands. A quasi-experimental design with a one-group pretest–posttest model was implemented with 40 tenth-grade students in Garut, Indonesia. Data were collected through a conceptual understanding test and a creativity rubric applied to student-designed posters. The results indicated an improvement in conceptual understanding (p < 0.001, Cohen’s d = 3.48, N-gain = 0.63, medium-category) and generally positive levels of creativity across most groups, particularly in relevance and originality. These findings suggest that Canva-supported guided inquiry provides a low-cost yet powerful pedagogical model that bridges cognitive and creative learning. The study contributes to theory by extending inquiry learning into digital platforms and to practice by offering scalable strategies for teachers. Future research is recommended to employ more comprehensive creativity assessments and to implement this approach across diverse educational contexts.Abstrak. Pembelajaran sains abad ke-21 menuntut penguasaan konsep sekaligus pengembangan kreativitas dan keterampilan berpikir tingkat tinggi untuk menghadapi isu global seperti perubahan lingkungan. Namun, siswa sering kesulitan menghubungkan pengetahuan ilmiah dengan konteks nyata sehingga pemahaman menjadi terfragmentasi dan kesempatan berekspresi kreatif terbatas. Penelitian ini bertujuan menganalisis efektivitas inkuiri terbimbing berbantuan Canva dalam meningkatkan pemahaman konsep dan kreativitas siswa pada topik perubahan lingkungan. Kebaruan penelitian ini terletak pada penggunaan guided inquiry berbantuan Canva sebagai pendekatan terintegrasi untuk mengembangkan pemahaman konseptual tingkat tinggi dan kreativitas yang selaras dengan tuntutan pembelajaran abad ke-21. Metode yang digunakan adalah kuasi eksperimen dengan desain pretest–posttest satu kelompok pada 40 siswa kelas X di Garut. Data dikumpulkan melalui tes pemahaman konsep dan rubrik kreativitas untuk menilai poster yang dibuat siswa. Hasil penelitian menunjukkan adanya peningkatan pemahaman konseptual (p < 0,001; Cohen’s d = 3,48; N-gain = 0,63 kategori sedang–tinggi) serta tingkat kreativitas yang secara umum positif pada sebagian besar kelompok, khususnya pada aspek relevansi dan orisinalitas. Temuan ini menegaskan bahwa Canva dapat menjadi media digital yang efektif, murah, dan mudah digunakan dalam mendukung inkuiri terbimbing. Penelitian ini berkontribusi pada teori dengan memperluas penerapan inkuiri ke platform digital serta pada praktik dengan menawarkan model pembelajaran yang relevan bagi tuntutan abad ke-21. Penelitian selanjutnya disarankan untuk menggunakan instrumen penilaian kreativitas yang lebih komprehensif dan menerapkan pendekatan ini pada konteks pendidikan yang lebih beragam.